2007
DOI: 10.1016/j.drugalcdep.2007.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Country of origin, age of drinking onset, and drinking patterns among Mexican American young adults

Abstract: This study examines relationships between country of origin, age of drinking onset,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 47 publications
1
14
1
Order By: Relevance
“…Differences in measures of ethnic identity, acculturation, study samples, and location make comparisons of findings between studies difficult. Further, the observed drinking patterns in the United States may reflect drinking practices among young people both in the United States and Mexico because Mexican migration is often neither linear nor unidirectional, which makes it difficult to associate alcohol use with migration to the United States within this population (Strunin et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in measures of ethnic identity, acculturation, study samples, and location make comparisons of findings between studies difficult. Further, the observed drinking patterns in the United States may reflect drinking practices among young people both in the United States and Mexico because Mexican migration is often neither linear nor unidirectional, which makes it difficult to associate alcohol use with migration to the United States within this population (Strunin et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In 2010, Hispanics comprised 14.1% of college undergraduates in the United States and from 1976 to 2010 the percentage of Hispanic college students increased more than any other racial/ethnic group (U.S. Department of Education, 2012). Over 16 million people residing in the United States were born in Mexico or are children of Mexican immigrants many of whom move back and forth between the United States to Mexico (Strunin, Edwards, Godette, & Heeren, 2007), maintain ongoing relationships in Mexico and are influenced by changes in Mexican cultural practices. A study examining how young people from different ethnic minority groups in the United States view the transition from adolescence to adulthood found African American, Asian and Latino American young people more likely than Whites to view the criteria reflecting obligation to others as necessary for adult status.…”
Section: Discussionmentioning
confidence: 99%
“…In past studies, country of origin has been an important proxy for acculturation and within-group variations in behaviors. Substance use perceptions and behaviors may vary depending on country of origin (Strunin et al 2007). Both Grant et al (2004) and Borges et al (2006) found that U.S.-born Mexican American adults were more at risk for alcohol-use disorder than Mexican-born immigrants in the U.S.…”
Section: Mexican-heritage Youths' Country Of Originmentioning
confidence: 99%
“…However, within this population, lifetime diagnoses of alcohol-use disorders, family history of alcohol dependence, acculturation stress, and lifetime diagnoses of major depressive disorder were all correlated with signifi cantly poorer quality sleep as indexed by the global score on the PSQI. An important fi nding in fi rst generation (i.e., immigrant generation) Mexican Americans is that alcohol use and other psychiatric disorders increase in frequency with time spent in the United States (Blume et al, 2009;Breslau et al, 2009;Burnam et al, 1987;Cherpitel et al, 2007;Golding and Burnam, 1990;Grant et al, 2004b;Kessler et al, 1994;Strunin et al, 2007;Vega et al, 1998Vega et al, , 2003. The increase in alcohol-use disorders and other psychiatric disorders seen in Mexican Americans that is associated with time spent living in the United States may not be related to changes in cultural identifi cation per se, but may also be the result of the "stress" of acculturation.…”
Section: Discussionmentioning
confidence: 99%